2008
DOI: 10.1002/adfm.200800705
|View full text |Cite
|
Sign up to set email alerts
|

Novel PEGylated Nanoassemblies Made of Self‐Assembled Squalenoyl Nucleoside Analogues

Abstract: This study describes a new simple method to obtain high loading of anticancer or antiviral nucleoside analogues into “stealth” poly(ethylene glycol) (PEG)‐coated nanoassemblies. These nanodevices are obtained by co‐nanoprecipitation in water of (i) squalenoyl prodrugs obtained by the bioconjugation of the natural lipid squalene with either the anticancer drug gemcitabine (Gem‐Sq) or the antiviral drug deoxycytidine (ddC‐Sq) with (ii) a PEG derivative of either cholesterol (Chol‐PEG) or squalene (Sq‐PEG). It wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 27 publications
4
57
0
Order By: Relevance
“…In previous work, the squalenoylation platform developed by our group was employed to design self-assembling nanomedicines derived from hydrophilic therapeutic agents, namely Gem, 2 ,3 -dideoxycytidine, and 2 ,3 -dideoxyinosine (Bekkara-Aounallah et al, 2008;Couvreur et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…In previous work, the squalenoylation platform developed by our group was employed to design self-assembling nanomedicines derived from hydrophilic therapeutic agents, namely Gem, 2 ,3 -dideoxycytidine, and 2 ,3 -dideoxyinosine (Bekkara-Aounallah et al, 2008;Couvreur et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…The cytotoxic activity of the drug-drug conjugate was demonstrated to be strongly dependent on its concentration -if the concentration is lower than the CAC value the cytotoxic activity is worse than the mixture of the two drugs but if the concentration is higher than the CAC value NPs showed a much better activity than the free drug mixture. This result suggested that the Our research group studied the formation of hetero-NPs by co-self-assembly of two squalene-based conjugates with the drugs paclitaxel (7) and cyclopamine (18) [42]. …”
Section: Page 13 Of 25mentioning
confidence: 96%
“…[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] Table 2 lists the commonly used nanomaterials in biomedical applications. The current review focuses predominantly on nanoparticles used in HIV-1 therapeutics.…”
Section: Types Of Nanomaterialsmentioning
confidence: 99%
“…the responsiveness of these nanostructures to specific stimuli through remote activation. 34,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] Inorganic particles are much smaller, typically less than 20 nm, and circulate easily in the bloodstream and are easily cleared via renal excretion. [42][43][44][45][46] Silica-based nanoparticles such as organically modified silica are known for their low toxicity and biocompatibility for targeted imaging and therapy.…”
Section: Types Of Nanomaterialsmentioning
confidence: 99%
See 1 more Smart Citation